Guest

Prove that: cot27°+cot32°+cot31°=cot27°×cot32°×cot31°

Prove that:
 
cot27°+cot32°+cot31°=cot27°×cot32°×cot31°

Grade:10

1 Answers

Yuvraj Singh
askIITians Faculty 75 Points
4 months ago
Ans:
Step-by-step explanation:

27+35+31=90

Cot90=0

Cot(27+35+31)=cot27+cot35+cot31 - cot27cot31cot35=0

Therefore,

Cot27+cot31+cot35=cot27.cot35.cot31

Hence proved

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free